1980
DOI: 10.1111/j.1365-2605.1980.tb00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Accessory Gland Infection and its Possible Role in Male Infertility

Abstract: The diagnosis of male adnexitis is difficult and the influence of this condition on fertility is still a matter of debate. With the intention to define diagnostic criteria a comprehensive study of biochemical and morphological features of semen, plus culture for microorganisms, was performed in patients who were assessed for infertility during a four year period. The following parameters were considered of diagnostic value: a) history of urogenital infection and/or abnormal rectal palpation. b) significant alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0
16

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(121 citation statements)
references
References 17 publications
1
104
0
16
Order By: Relevance
“…Leukocytospermia is an important indicator of male urogenital tract infections and/or inflammations [27], and is considered a contributing cause of male infertility [1] because of excessive ROS production and release [3]. Imbalances between ROS production and semen antioxidant capacity will lead to oxidative stress [9,10], which will ultimately result in oxidation of membrane polyunsaturated fatty acids [14,15], loss of mitochondrial membrane potential [16], and single and double strand DNA fragmentation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytospermia is an important indicator of male urogenital tract infections and/or inflammations [27], and is considered a contributing cause of male infertility [1] because of excessive ROS production and release [3]. Imbalances between ROS production and semen antioxidant capacity will lead to oxidative stress [9,10], which will ultimately result in oxidation of membrane polyunsaturated fatty acids [14,15], loss of mitochondrial membrane potential [16], and single and double strand DNA fragmentation [17].…”
Section: Discussionmentioning
confidence: 99%
“…The major difficulty in interpreting microbiological findings is the presence of contaminating, indig enous microbiota, or of inhibitory substances known to be present in the prostate secretions, as well as previous courses of antibiotics (77). The diagnosis of semen bacterial infection may be confirmed by semen quantitative bacteriological cultures.…”
Section: Pathogenicity Of Some Bacterial Species On Spermmentioning
confidence: 99%
“…It is also the primary bacteria associated with prostatitis and epididymitis (77). E. coli has a passive effect on sperm motility and acrosomal function (48).…”
Section: The Effects Of Bacterial Infection On Sperm Parametersmentioning
confidence: 99%
“…Examining 500 ejaculates, Comhaire et al [26] found a significant positive association between the presence of more than lo6 peroxidase-positive WBC/mL and the frequency of pathogenic isolates. Furthermore, in some studies antibiotic treatment of men with leukocytospermia seems to have caused disappearance of seminal leukocytes and improved sperm motility and pregnancy outcome (Table 7).…”
Section: Leukocytospermia-an Indicator Of Male Reproductive Tract Infmentioning
confidence: 99%